If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -9 + 3x = 9 + -1x Reorder the terms: -9 + 2x + 3x = 9 + -1x Combine like terms: 2x + 3x = 5x -9 + 5x = 9 + -1x Solving -9 + 5x = 9 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. -9 + 5x + x = 9 + -1x + x Combine like terms: 5x + x = 6x -9 + 6x = 9 + -1x + x Combine like terms: -1x + x = 0 -9 + 6x = 9 + 0 -9 + 6x = 9 Add '9' to each side of the equation. -9 + 9 + 6x = 9 + 9 Combine like terms: -9 + 9 = 0 0 + 6x = 9 + 9 6x = 9 + 9 Combine like terms: 9 + 9 = 18 6x = 18 Divide each side by '6'. x = 3 Simplifying x = 3
| 103-1x+2x=6x-7 | | 1y=6-4y | | 12+6x=84 | | 8u/4+u=13 | | 2x+8=2x-3 | | (9-m)+4m+6= | | 3t^2+2+8t+3=0 | | 14x+8x+4=180 | | 0.2x+3.4+0.8=4 | | 4p^2+12+9=0 | | -5r+2r=-18 | | x^2+2=4x+6 | | 2x+x+14+x-38=180 | | 6t^2+2t-20= | | -6p^2=-510 | | y-83=3y-23 | | 8x-7=8(x-2) | | 7/12+8/12= | | 12x-1-7x=17 | | 14x+155=1 | | 3+w=41*2 | | 7x+4x+3+7=7x+3+3x | | 5(x-41)=75 | | c-823=-23c-7 | | 6q=24q+7 | | 8x+1+5x-2=90 | | -3x+69=x+189 | | 8(3a+6)=9(2a-2) | | 8.95m+.06=0m+.10 | | 6(y-9)=4(y-5) | | 2xsquared+5x+4=0 | | 7q+14=5(2q)-55 |